Implementasi Media Pembelajaran Google Form dalam Meningkatkan Kemampuan Hafalan Al-Qur’an Santri di Pondok Pesantren Tahfiz Al-Habibi - Reyin, Anis Sunnai; Daulai, Afrahul Fadhila (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
The background of this research stems from the limited use of digital media in Al-Qur'an memorization evaluation activities in Islamic boarding schools. This study aims to explore the implementation of Google Forms as an innovative medium for evaluating Al-Qur'an memorization at the Tahfiz Al-Habibi Islamic Boarding School. This research uses a descriptive qualitative approach to gain an in-depth understanding of the experiences of teachers and students in utilizing digital technology to support the tahfizh learning process. The descriptive method was chosen because it is able to present data systematically, factually, and accurately regarding the dynamics of tahfizh learning that takes place. Research data was obtained through observation of activities, in-depth interviews, and documentation of student memorization evaluation results conducted periodically using Google Forms. The results of the study show that the use of Google Forms makes it easier for teachers to monitor the progress of students' memorization in real-time, provide quick feedback, and simplify evaluation administration. On the other hand, students feel an increase in motivation, discipline in muroja'ah, and independence in the learning process. This study concludes that Google Forms not only functions as a learning medium but also as an innovative evaluation strategy that can modernize the tahfizh learning system in Islamic boarding schools. The integration of this technology is considered relevant in strengthening the quality of Al-Qur'an learning while addressing the challenges faced by Islamic boarding schools in the modern era.Keywords - Google Forms, Learning Media, Qualitative Research, Qur’an Memorization, Tahfiz Education.